Modified chitosan aerogel and its preparation and application

TW202637279AActive Publication Date: 2026-09-16NATIONAL ILAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
TW114109327
Authority / Receiving Office
TW · TW
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2026-09-16
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

Existing adsorption technologies for removing heavy metals and antibiotics from wastewater, such as chitosan aerogel and metal-organic frameworks, face limitations in adsorption capacity, difficulty in material recovery, and low regeneration rates, leading to secondary pollution and high treatment costs.

Method used

A modified chitosan aerogel combining zinc-based metal-organic frameworks (Zn-MOF) with chitosan aerogel (CA) enhances specific surface area and pore size, improving recyclability and adsorption efficiency for Cu(II) and oxytetracycline (OTC) through a method involving dissolution, crosslinking, and MOF growth on the chitosan aerogel surface.

Benefits of technology

The modified chitosan aerogel effectively removes Cu(II) and OTC with adsorption efficiencies up to 95.1% and 91.8%, respectively, while enabling recyclability and reducing treatment costs and environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure TWG2TA001075911_001
    Figure TWG2TA001075911_001
  • Figure TWG2TA001075911_002
    Figure TWG2TA001075911_002
  • Figure TWG2TA001075911_003
    Figure TWG2TA001075911_003
Patent Text Reader

Abstract

A modified chitosan aerogel and its preparation and application, by combining zinc-based metal organic frameworks (Zn-MOF) with chitosan aerogel (CA), the high specific surface area and small pore size of Zn-MOF with the functional adsorption characteristics of chitosan, the recycling problem of Zn-MOF is improved, the modified chitosan aerogel can not only effectively remove Cu(II) ions and oxytetracycline (OTC) from wastewater, but also can enhance the recyclability of the adsorbent through appropriate recycling and regeneration techniques, so as to reduce treatment costs and environmental burdens, which has good application prospects and is helpful to promote the realization of water resource recycling and environmental protection goals.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to chitosan aerogels, and more particularly to modified chitosan aerogels modified with metal-organic frameworks, their preparation methods and applications. [Previous Technology]

[0002] The global water shortage problem is becoming increasingly serious, especially under the influence of extreme climate change, which has led to drastic changes in precipitation patterns in some regions, resulting in frequent droughts and further exacerbating the imbalance between water supply and demand. The United Nations' Sustainable Development Goals (SDGs) proposed in 2015, with SDG 6 emphasizing clean water and sanitation, aim to ensure that the global population has access to clean water resources and promote sustainable water management. However, globally available freshwater resources account for only 0.007%, making the efficient recycling and reuse of wastewater a key issue in water resource management.

[0003] It is worth noting that industrial, agricultural, and livestock production processes generate large amounts of wastewater containing pollutants. For example, livestock wastewater, mainly from cleaning farmhouses and animal manure, contains high concentrations of heavy metals and antibiotics, such as copper ions (Cu(II)) and oxytetracycline (OTC). Since Cu(II) and OTC are often added to livestock feed to promote growth, most of these substances are excreted unabsorbed after animal digestion, thus polluting the wastewater. For instance, in Taiwan, the concentration of Cu(II) in pig farm wastewater ranges from approximately 4.7 mg / L to 59.4 mg / L, far exceeding Taiwan's copper ion discharge standards (3.0 mg / L) and drinking water standards (1.0 mg / L). Furthermore, the concentration of OTC varies greatly in different environments, potentially affecting groundwater and soil ecology, and long-term accumulation may even pose a potential risk to human health.

[0004] Currently, technologies for removing heavy metals and antibiotic pollutants from water include precipitation, adsorption, oxidation, nanofiltration, biodegradation, advanced oxidation technologies, photocatalytic degradation, and electrochemical treatment. Among these, adsorption technology has become a widely used treatment method due to its advantages such as simple operation, no secondary pollution, and low cost. Current adsorption materials include chitosan aerogel (CA) and metal-organic frameworks (MOFs). Chitosan aerogel (CA) contains a large number of amine and hydroxyl functional groups, which can effectively adsorb heavy metal pollutants. Because of its light weight, it can float on the water surface and is easy to separate. However, chitosan aerogel has a low specific surface area and a large pore size, which affects its adsorption capacity. Zinc metal-organic frameworks (Zn-MOFs) have a high specific surface area and microporous structure, and the Zn and N in Zn-MOFs can form bonds with pollutants, giving them good adsorption capacity for heavy metals and antibiotics. However, Zn-MOFs are often in powder form, making them difficult to separate from water bodies after use, which may lead to secondary pollution problems.

[0005] In addition, although the aforementioned existing adsorption technologies can effectively remove Cu(II) and OTC from wastewater, they generally suffer from limited adsorption capacity, difficulty in material recovery, or low regeneration rate. Therefore, it is necessary to propose a highly efficient and recyclable adsorption material to overcome the aforementioned technical problems. [Summary of the Invention]

[0006] To overcome the above-mentioned technical problems, the purpose of this invention is to provide a modified chitosan aerogel, its preparation method and application. By combining zinc-based metal-organic framework (Zn-MOF) with chitosan aerogel (CA), the high specific surface area and small pore size of Zn-MOF are combined with the functional group adsorption characteristics of chitosan, and the recycling problem of Zn-MOF is improved. This invention's modified chitosan aerogel can not only effectively remove divalent copper (Cu(II)) ions and oxytetracycline (OTC) from wastewater, but also improve the recyclability of the adsorbent through appropriate recycling and regeneration technologies, thereby reducing treatment costs and environmental burden. It has good application prospects and helps to promote the realization of water resource recycling and environmental protection goals.

[0007] To achieve the above objectives, the present invention provides a modified chitosan aerogel, comprising: a zinc-based modified chitosan aerogel (Zn-MCA) modified with a zinc-based metal-organic framework (Zn-MOF); the zinc-based modified chitosan aerogel, when measured by Fourier transform infrared spectroscopy (FTIR), has absorption peaks in the following wavenumber regions: 3100 cm⁻¹ to 3400 cm⁻¹, 2950 cm⁻¹ ± 4 cm⁻¹, 1658 cm⁻¹ ± 4 cm⁻¹, 1592 cm⁻¹ ± 4 cm⁻¹, 1383 cm⁻¹ ± 4 cm⁻¹, 1020 cm⁻¹ ± 4 cm⁻¹, 997 cm⁻¹ ± 4 cm⁻¹, 757 cm⁻¹ ± 4 cm⁻¹, and 691 cm⁻¹ ± 4 cm⁻¹.

[0008] In the embodiments of the present invention, the zinc-modified chitosan aerogel (Zn-MCA) exhibited characteristic peaks at the following 2θ (two-theta) positions when analyzed by X-ray diffraction (XRD): 21.0°±0.5°, 7.3°±0.5°, 10.7°±0.5°, 12.9°±0.5°, 13.8°±0.5°, 15.3°±0.5°, 17.8°±0.5°, 26.0°±0.5°, and 29.2°±0.5°.

[0009] In the embodiment of the present invention, when the zinc-based modified chitosan aerogel (Zn-MCA) was measured by X-ray photoelectron spectrometry (XPS), the atomic percentage of the surface elements of the zinc-based modified chitosan aerogel was found to be 64.8±5% C 1s, 14.2±5% N 1s, 17.3±5% O 1s and 3.7±5% Zn 2p.

[0010] To achieve the above objectives, the present invention further provides a method for preparing modified chitosan aerogel, the steps of which include: a dissolution and crosslinking step: adding chitosan powder to an aqueous organic acid solution to completely dissolve the chitosan and form a chitosan solution; adding a crosslinking agent to the chitosan solution to carry out a crosslinking reaction, stirring evenly, and then treating it in an ultrasonic oscillation environment to remove air bubbles in the solution, and allowing it to stand until a solid hydrogel is formed; a hydrogel curing and drying step: taking out the solid hydrogel, immersing it in an alkaline solution to cure the material, and washing it with deionized water until neutral; subsequently, freezing the cured material, and then freeze-drying it to obtain a chitosan aerogel; a metal precursor treatment step: dissolving a zinc salt compound in an organic solvent to form a zinc precursor solution; contacting the chitosan aerogel with the zinc precursor solution to fully adsorb, forming a chitosan aerogel containing zinc ions; Metal-organic framework (MOF) growth steps: Imidazole compounds are dissolved in an organic solvent to form a MOF ligand solution, which is then added to the zinc-containing chitosan aerogel to allow MOF crystals to grow on the surface of the chitosan aerogel, thus obtaining a preliminary material. Cleaning and drying steps: The preliminary material is washed with deionized water to remove unreacted MOF precursors, and then freeze-dried to obtain a zinc-modified chitosan aerogel (Zn-MCA), one of the composite chitosan aerogels made of zinc-based metal-organic framework (Zn-MOF). The Zn-MOF content in the chitosan aerogel is saturated; based on a total weight of 100 wt% for the zinc-modified chitosan aerogel (Zn-MCA), the loading of Zn-MOF in the chitosan aerogel ranges from 20 wt% to 50 wt%.

[0011] In this embodiment of the invention, in the dissolution and crosslinking step, the aqueous organic acid solution may be selected from acetic acid (CH3COOH), formic acid (CH2O2), or lactic acid (C3H6O3); the crosslinking agent may be selected from glutaraldehyde (C5H8O2), pentapentine (C5H8O2), or an epoxy compound. Specifically, in the dissolution and crosslinking step, the aqueous organic acid solution is acetic acid with a concentration of 0.2M; the crosslinking agent is glutaraldehyde.

[0012] In this embodiment of the invention, during the hydrogel curing and drying step, the alkaline solution may be selected from sodium hydroxide (NaOH) or potassium hydroxide (KOH). Specifically, during the hydrogel curing and drying step, the alkaline solution is 0.1M sodium hydroxide (NaOH).

[0013] In this embodiment of the invention, in the metal precursor treatment step, the zinc salt compound may be selected from zinc nitrate hexahydrate (Zn(NO3)2·6H2O), zinc chloride (ZnCl2), or zinc acetate (CH3CO2)2Zn); the organic solvent may be an alcohol solution. Specifically, in the metal precursor treatment step, the zinc salt compound is zinc nitrate hexahydrate; the organic solvent is a methanol (CH3OH) solution.

[0014] In this embodiment of the invention, during the metal-organic framework (MOF) growth step, the imidazole compound may be selected from 2-methylimidazole (C4H6N2) or 1,2,4-triazole (C2H3N3); the organic solvent may be an alcohol solution. Specifically, during the MOF growth step, the imidazole compound is 2-methylimidazole; the organic solvent is a methanol (CH3OH) solution.

[0015] In the embodiments of the present invention, based on a total weight of 100 wt% of the zinc-modified chitosan aerogel (Zn-MCA), the loading range of Zn-MOF in the chitosan aerogel can be 20 wt%, 23 wt%, 26 wt%, 29 wt%, 32 wt%, 35 wt%, 38 wt%, 41 wt%, 44 wt%, 47 wt%, or 50 wt%. The loading range of Zn-MOF in the chitosan aerogel can be within any two of the above values, but is not limited to them. Specifically, based on a total weight of 100 wt% of the zinc-modified chitosan aerogel (Zn-MCA), the loading range of Zn-MOF in the chitosan aerogel can be 35 wt%.

[0016] To achieve the above objective, the present invention further provides the use of the modified chitosan aerogel as described above or the modified chitosan aerogel prepared by the method for adsorbing divalent copper (Cu(II)) ions in waste liquid; wherein, when the initial concentration of the divalent copper ions is 1 ppm to 20 ppm, the pH value of the waste liquid is 2 to 5, the dosage of the zinc-based modified chitosan aerogel in each liter of waste liquid is 0.25 g to 2.0 g, the adsorption temperature is 15 °C to 45 °C, and the adsorption time is 180 minutes, the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for the Cu(II) ions reaches 95.1%.

[0017] In the embodiments of the present invention, the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for the Cu(II) ion can be greater than 0% to less than or equal to 95.1%. Specifically, the adsorption efficiency of the zinc-based modified chitosan aerogel for the Cu(II) ion can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95.1%; the adsorption efficiency of the zinc-based modified chitosan aerogel for the Cu(II) ion can be within the range of any two of the above values, but is not limited to this.

[0018] In the embodiments of the present invention, when the modified chitosan aerogel is used to adsorb divalent copper ions in waste liquid, the dosage of the zinc-based modified chitosan aerogel per liter of waste liquid can be 0.25 g, 1.0 g, 1.5 g, or 2.0 g; the dosage of the zinc-based modified chitosan aerogel per liter of waste liquid can be within the range of any two of the above values, but is not limited thereto. Preferably, the dosage of the zinc-based modified chitosan aerogel per liter of waste liquid is 1.0 g.

[0019] In the embodiments of the present invention, when the modified chitosan aerogel is used to adsorb divalent copper ions in waste liquid, the initial concentration of the divalent copper ions can be 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm, 6 ppm, 7 ppm, 8 ppm, 9 ppm, 10 ppm, 11 ppm, 12 ppm, 13 ppm, 14 ppm, 15 ppm, 16 ppm, 17 ppm, 18 ppm, 19 ppm, or 20 ppm; the initial concentration of the divalent copper ions can be within the range of any two of the above values, but is not limited thereto. Preferably, the initial concentration of the divalent copper ions can be 1 ppm.

[0020] In the embodiments of the present invention, when the modified chitosan aerogel is used to adsorb divalent copper ions in waste liquid, the adsorption temperature can be 15°C, 17.5°C, 20°C, 22.5°C, 25°C, 27.5°C, 30°C, 32.5°C, 35°C, 37.5°C, 40°C, 42.5°C, or 45°C; the adsorption temperature can be within the range of any two of the above values, but is not limited to this. Preferably, the adsorption temperature is 25°C.

[0021] In the embodiments of the present invention, when the modified chitosan aerogel is used to adsorb divalent copper ions in waste liquid, the pH value of the waste liquid can be 2, 2.5, 3, 3.5, 4, 4.5, or 5; the pH value of the waste liquid can be within the range formed by any two of the above values, but is not limited to this. Preferably, the pH value of the waste liquid can be 5.

[0022] To achieve the above objectives, the present invention further provides the use of the modified chitosan aerogel as described above or the modified chitosan aerogel prepared by the method for adsorbing oxytetracycline (OTC) in waste liquid; wherein, when the initial concentration of oxytetracycline is 1 ppm to 8 ppm, the pH value of the waste liquid is 3 to 9, the dosage of the zinc-based modified chitosan aerogel in each liter of waste liquid is 0.25 g to 2.0 g, the adsorption temperature is 15 °C to 45 °C, and the adsorption time is 120 minutes, the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for oxytetracycline reaches 91.8%.

[0023] In the embodiments of the present invention, the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for oxytetracycline can be greater than 0% to less than or equal to 91.8%. Specifically, the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for oxytetracycline can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 91.8%; the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for oxytetracycline can be within the range of any two of the above values, but is not limited thereto.

[0024] In an embodiment of the present invention, when the modified chitosan aerogel is used to adsorb oxytetracycline in waste liquid, the dosage of the zinc-based modified chitosan aerogel per liter of waste liquid can be 0.25 g, 1.0 g, 1.5 g, or 2.0 g. The dosage of the zinc-based modified chitosan aerogel per liter of waste liquid can be within the range of any two of the above values, but is not limited thereto. Preferably, the dosage of the zinc-based modified chitosan aerogel per liter of waste liquid is 1.0 g.

[0025] In an embodiment of the present invention, when the modified chitosan aerogel is used to adsorb oxytetracycline (OTC) in waste liquid, the pH value of the waste liquid can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, or 9; the pH value of the waste liquid can be within the range formed by any two of the above values, but is not limited to this. Preferably, the pH value of the waste liquid can be 5.

[0026] In the embodiments of the present invention, when the modified chitosan aerogel is used to adsorb oxytetracycline (OTC) in waste liquid, the initial concentration of the oxytetracycline can be 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm, 6 ppm, 7 ppm, 8 ppm, 9 ppm, 10 ppm, 11 ppm, 12 ppm, 13 ppm, 14 ppm, 15 ppm, 16 ppm, 17 ppm, 18 ppm, 19 ppm, or 20 ppm; the initial concentration of the oxytetracycline can be within the range of any two of the above values, but is not limited thereto. Preferably, the initial concentration of the oxytetracycline can be 1 ppm.

[0027] In the embodiments of the present invention, when the modified chitosan aerogel is used to adsorb oxytetracycline (OTC) in waste liquid, the adsorption temperature can be 15°C, 17.5°C, 20°C, 22.5°C, 25°C, 27.5°C, 30°C, 32.5°C, 35°C, 37.5°C, 40°C, 42.5°C, or 45°C; the adsorption temperature can be within the range of any two of the above values, but is not limited to this. Preferably, the adsorption temperature is 25°C.

[0028] In the embodiments of the present invention, the wastewater refers to livestock wastewater, industrial wastewater or other water bodies containing heavy metals and / or antibiotics.

Implementation Method

[0029] To facilitate understanding of the present invention, the following description is provided in conjunction with the invention drawings and embodiments.

[0030] Preparation of Adsorbent Materials

[0031] Preparation Example 1: Preparation of Chitosan Aerogel (CA)

[0032] 1 g of chitosan ((C6H11O4N)n) powder was added to 100 mL of 0.2 M acetic acid (CH3COOH) and stirred until completely dissolved. 10 mL of glutaraldehyde (C5H8O2) was added dropwise to the chitosan solution to carry out the cross-linking reaction. The well-mixed solution was placed in a centrifuge bottle and placed in an ultrasonic shaker for 10 minutes to remove air bubbles. After standing for one day, the solution formed a solid hydrogel. This hydrogel was removed and immersed in 0.1 M sodium hydroxide (NaOH), and then washed with deionized water until neutral. The washed material was frozen in a freezer and then freeze-dried to prepare chitosan aerogel (CA).

[0033] Preparation Example 2: Preparation of Zinc-based Metal-Organic Framework Materials (Zn-MOF)

[0034] 0.5 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 2 g of 2-methylimidazole (C4H6N2) were dissolved separately in 25 mL of methanol (CH3OH) solution. After complete dissolution, the 2-methylimidazole methanol solution was added dropwise to the zinc nitrate hexahydrate methanol solution to induce the formation of zinc-based metal-organic framework (Zn-MOF) crystals, and the mixture was stirred overnight. The material was washed three times with methanol, and the white precipitate was separated from the methanol by centrifugation. The precipitate was dried in an oven at 80 °C. After cooling, the material was ground into powder to obtain the zinc-based metal-organic framework (Zn-MOF), which was then stored in a drying oven.

[0035] Preparation Example 3: Preparation of Zinc-based Modified Chitosan Aerogel (Zn-MCA)

[0036] 0.5 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) was dissolved in 25 mL of methanol (CH3OH) solution. After complete dissolution, the dissolved solution was placed into the prepared chitosan aerogel (CA) to fill the surface of the chitosan aerogel with the zinc nitrate hexahydrate methanol solution. Then, 2 g of 2-methylimidazole (C4H6N2) was dissolved in 25 mL of methanol solution. After complete dissolution, the dissolved solution was dropped onto the surface of the chitosan aerogel and stirred overnight to allow the crystals of the zinc-based metal-organic framework material (Zn-MOF) to grow completely on the surface of the chitosan aerogel. Excess Zn-MOF on the surface was rinsed with deionized water. After freezing, the material was freeze-dried to obtain a zinc-modified chitosan aerogel (Zn-MCA) material of Zn-MOF composite chitosan aerogel. The Zn-MOF content in the Zn-MCA material was saturated, and the loading of Zn-MOF on the surface of the chitosan aerogel was about 35 wt%.

[0037] The above describes the preparation methods of chitosan aerogel (CA), zinc-based metal-organic framework (Zn-MOF) and zinc-based modified chitosan aerogel (Zn-MCA). The names, chemical formulas, purities and pharmaceutical companies of the experimental reagents used in the above preparation methods are as follows: (1) Acetic acid (CH3COOH), 99.7%, purchased from Nippon Pharmaceutical Industries Co., Ltd.; (2) Glutaraldehyde (C5H8O2), 25% to 50%, purchased from Nippon Pharmaceutical Industries Co., Ltd.; (3) Copper nitrate trihydrate (Cu(NO3)2·3H2O), 99%, purchased from Nippon Pharmaceutical Industries Co., Ltd.; (4) Zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 95%, purchased from Nippon Pharmaceutical Industries Co., Ltd.; (5) Methanol (CH3OH), 99.8%, purchased from Honeywell. Riedel-de-Haën™; (6) Ethanol (C2H6O), 99.8%, purchased from Honeywell Riedel-de-Haën™; (7) Oxytetracycline (C22H24N2O9), 99%, purchased from Sigma-Aldrich, USA; (8) 2-Methylimidazole (C4H6N2), 99%, purchased from Sigma-Aldrich, USA; (9) Hydrochloric acid (HCl), 38%, purchased from JTBaker; (10) Nitric acid (HNO3), 69%, purchased from JTBaker; (11) Chitosan ((C6H11O4N)n), 99% ACROS ORGANICS; (12) Sodium hydroxide (NaOH), 95%, purchased from Xilong Scientific Co., Ltd.

[0038] Characteristic Analysis of Adsorption Materials

[0039] Experimental Example 1: Measurement by Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray Spectroscopy (EDS)

[0040] Experimental Example 1 uses SEM and EDS to analyze the materials prepared in Preparation Examples 1 and 3 and their adsorbed surfaces of divalent copper (Cu(II)) and / or oxytetracycline (OTC) to explore the structural composition and elemental distribution.

[0041] The SEM measurement involves fixing the material to be tested onto carbon cloth, irradiating the material with Pt light to increase the conductivity of the material surface, placing it inside an SEM, and irradiating the material surface with an electron beam. The instrument images the signal reflected from the material surface. The structural features of the material surface are observed at magnifications of 100x and 500x. The scanning electron microscope used in this experiment was purchased from Tescan.

[0042] EDS measurement involves irradiating the surface of the material under test with an electron beam. Because different atoms reflect different X-rays, the instrument receives different X-rays to analyze the elemental distribution and content on the material surface, and calculates the weight percentage and atomic percentage of the elements. The energy-scattering X-ray spectroscopy instrument used in this experiment was purchased from Tescan.

[0043] As shown in Figures 1A and 1B, chitosan is cross-linked with glutaraldehyde to form chitosan aerogel (CA) (Preparation Example 1), exhibiting a 3D porous structure. Numerous pores provide channels for pollutant adsorption, and adjacent pores provide many pathways, enabling rapid transport of pollutants within the chitosan aerogel. Compared to the smooth surface of the chitosan aerogel, as shown in Figures 1C and 1D, the surface of Zn-MCA modified with Zn-MOF (Preparation Example 3) is rougher, with many white protrusions clearly visible on the Zn-MCA surface, confirming the successful in-situ growth of Zn-MOF on the chitosan aerogel surface. SEM images of the adsorbed Cu(II) and / or OTC Zn-MCA are shown in Figures 2A and 2E. There is no significant structural change in Zn-MCA before and after adsorption; it maintains its 3D porous structure. However, the surface of the adsorbed Zn-MCA exhibits even more protrusions.

[0044] The elemental composition of the material surface was analyzed using EDS elemental analysis, as shown in Table 1. The EDS elemental analysis results in Table 1 show that the chitosan aerogel contains only C, N, and O elements; while Zn-MCA contains C, N, O, and Zn elements, confirming that Zn-MOF has been successfully grown on the surface of the chitosan aerogel. Furthermore, EDS elemental analysis revealed that Zn-MCA contains Cu elements after adsorption, indicating that Cu(II) has been successfully adsorbed by the aerogel. Specifically, the chitosan aerogel contains C (48.43%), N (7.12%), and O (44.45%) elements; Zn-MCA contains C (40.63%), N (28.02%), O (23.52%), and Zn (7.83%) elements. Chitosan aerogel is combined with Zn-MOF to form Zn-MCA, which increases the N element content by 20.9%. The N element on the imidazole ring in Zn-MCA contains many unshared electron pairs, which can provide a large number of active sites to facilitate the adsorption of pollutants.

[0045] Table 1: EDS elemental analysis of materials (CA, Zn-MCA) obtained in Preparation Examples 1 and 3 Elemental test material C (K) N (K) O (K) Zn (L) Cu (L) total CA W % 48.43 7.12 44.45 -- -- 100 A % 55.09 6.95 37.96 -- -- 100 Zn-MCA W % 40.63 28.02 23.52 -- -- 100 A % 46.99 27.77 20.42 -- -- 100 Zn-MCA-OTC W % 46.67 18.93 30.16 4.24 -- 100 A % 54.07 18.80 26.23 0.90 -- 100 Zn-MCA-Cu W % 35.36 26.77 30.31 0.76 6.80 100 A % 41.45 26.91 28.08 0.16 3.40 100 Zn-MCA-Cu-OTC W % 47.05 13.21 31.65 5.18 2.90 100 A % 56.25 13.54 28.41 1.14 0.66 100 (1) W% and A% are the weight percentage and atomic percentage, respectively. (2) K and L are the X-ray categories of the scan.

[0046] Experimental Example 2: Determination by Fourier Transform Infrared Spectroscopy (FTIR)

[0047] In Experimental Example 2, the materials prepared in Examples 1 to 3 were placed above an infrared light source and scanned at 650 cm⁻¹ to 4000 cm⁻¹. After passing through the beam splitter, the infrared light formed infrared beams with energy differences due to the interference between the moving and fixed mirrors. These beams were then absorbed by different functional groups on the material surface, and finally, the detector generated an infrared absorption spectrum through Fourier transform. The Fourier transform infrared spectrometer used in this experiment was purchased from Perkin Elmer Inc., model Spectrum 100.

[0048] To analyze the surface functional groups of the CA, Zn-MOF, and Zn-MCA materials prepared in Examples 1 to 3, FTIR was used to analyze the three materials at 650 cm⁻¹ to 4000 cm⁻¹ in this experiment, as shown in Figure 3A. The common functional groups are the -OH functional group located at 3100 cm⁻¹ to 3400 cm⁻¹, the CH bending vibration functional group at 2950 cm⁻¹, and the NH stretching vibration functional groups at 1592 cm⁻¹ and 1383 cm⁻¹, respectively. The C=O functional group at 1658 cm⁻¹ belongs to the amide bond stretching vibration functional group, and the CO stretching vibration functional group at 1020 cm⁻¹ is a characteristic functional group of CA. The CN bending vibration functional group at 997 cm⁻¹, the Zn-O stretching vibration functional group at 757 cm⁻¹, and the Zn-N stretching vibration functional group at 691 cm⁻¹ are characteristic functional groups of Zn-MOF. The characteristic functional groups of CA and Zn-MOF can be seen in the FTIR analysis spectrum of Zn-MCA, indicating that Zn-MCA has been successfully composited using CA and Zn-MOF materials.

[0049] The FTIR of Cu(II) and OTC before and after adsorption using Zn-MCA is shown in Figure 3B. After adsorption of Cu(II) and OTC, it was found that the peak values ​​of the -OH functional group (3100-3400 cm⁻¹), the NH functional group (1592 cm⁻¹), and the CN functional group (997 cm⁻¹) decreased significantly after adsorption. The main reason is the electrostatic interaction between OTC and the positively charged amine group, which weakens the peak value of the NH functional group. In addition, during the adsorption process, pollutants form H bonds and undergo misalignment reactions with functional groups such as hydroxyl and amine groups, which also leads to a significant decrease in the peak values ​​of the three characteristic functional groups.

[0050] Experimental Example 3: Measurement by X-ray Diffractometers (XRD)

[0051] In Experiment 5, the materials prepared in Preparation Examples 1 to 3 were placed on a stage and irradiated with X-rays. The atoms of the material scattered the light, and the different scattered waves interfered with each other, eventually forming diffracted waves. The crystal orientation of the material was measured at a scan rate of 1° per minute from 5° to 40°, and the measured characteristic peak values ​​of the material were compared with standard charts and literature. The X-ray diffractometer used in this experiment was purchased from BRUKER Corporation, USA, model D2 PHASER.

[0052] XRD was used to analyze the crystal orientation of Zn-MOF, CA, and Zn-MCA in the range of 5° to 40°. The analysis results are shown in Figure 4A. The characteristic peaks of Zn-MOF prepared in this invention at 7.1, 10.2, 12.5, 14.5, 16.2, 17.8, 21.9, 24.3, 26.4, and 29.4° all conform to the ZIF-8 characteristic peaks of JCPDS: 00-062-1030, confirming the successful preparation of Zn-MOF. As shown in Figure 4B, CA has a broad peak at 20.9°, and this characteristic peak was found at 21.0° in Zn-MCA. Characteristic peaks belonging to Zn-MOF were found at 7.3, 10.7, 12.9, 13.8, 15.3, 17.8, 26.0 and 29.2° of Zn-MCA, indicating that Zn-MOF and CA successfully recombine to form Zn-MCA.

[0053] Experimental Example 4: Measurement using a High-resolution X-ray Photoelectron Spectrometer (XPS)

[0054] The XPS analysis of this invention was performed with the assistance of the Precious Instruments Management Center of National Chung Cheng University. Under vacuum conditions, X-rays were used to irradiate the material surface, and lenses were used to collect photoelectrons emitted by atoms on the material surface. The electron energy and intensity were analyzed, and the functional groups corresponding to different electron binding energies were compared with those in the literature. All materials tested in this invention underwent full-energy spectroscopy scanning first, followed by individual elemental scanning. The high-resolution electron spectrometer used in this experiment was purchased from Agilent Technologies Taiwan, model 4100 MP-AES.

[0055] The binding energy of CA, Zn-MCA (before and after modification), and Zn-MCA before and after adsorption was analyzed by XPS to explore the proportion distribution of different functional groups before and after adsorption and whether new functional groups were generated. Full-energy spectroscopy was performed at 284.8, 395.7, 533.4, 930.4, and 1022.0 eV, and the atomic percentages of C 1s, N 1s, O 1s, Cu 2p, and Zn 2p were measured, as shown in Figure 5. For CA, the atomic percentages were C 1s (76.0%), N 1s (3.8%), and O 1s (20.2%). For Zn-MCA, the atomic percentages were C 1s (64.8%), N 1s (14.2%), O 1s (17.3%), and Zn 2p (3.7%). After Zn-MOF is combined with CA, compared with CA, Zn-MCA increases the proportion of Zn element, the proportion of C and O elements decreases, and the proportion of N element increases significantly. It can be seen that Zn-MOF is successfully attached to CA material, as shown in Table 2.

[0056] After Cu(II) adsorbed by Zn-MCA, the contents of C 1s (63.0%), N 1s (13.5%), O 1s (19.9%), Zn 2p (2.7%) and Cu 2p (0.9%) were measured, indicating that the Cu(II) content on the material increased after adsorption, that is, Cu(II) was successfully adsorbed on Zn-MCA; after OTC adsorption, the contents of C 1s (63.3%), N 1s (10.0%), O 1s (23.1%) and Zn 2p (3.6%) were measured, indicating that the O / C ratio on the material increased after adsorption (from 0.27 before adsorption to 0.36 after adsorption), that is, OTC was successfully adsorbed on Zn-MCA. After simultaneous adsorption of Cu(II) and OTC, the proportions of C 1s (61.2%), N 1s (13.2%), O 1s (20.3%), Zn 2p (2.5%), and Cu 2p (2.8%) were measured. This indicates that after adsorption of Cu(II) and OTC, the proportions of C, N, and Zn elements decreased in Zn-MCA, while the proportion of O element increased. During adsorption, the functional groups containing C and N interact with the pollutants, leading to a decrease in the proportions of C and N elements. The decrease in the proportion of Zn element is due to the slight dissolution of Zn(II) in water and the ion exchange reaction during Cu(II) adsorption. The increase in the proportion of O element after Cu(II) adsorption is mainly due to the formation of complexes between Cu(II) and O, resulting in an increase in the content of oxygen-containing functional groups. After OTC adsorption, the presence of O atoms in the OTC structure also contributes to the increase in the proportion of O element.

[0057] Table 2: Atomic percentages of materials prepared in Preparation Examples 1 to 3 before and after adsorption of divalent copper (Cu(II)) and / or oxytetracycline (OTC) Atoms (%) of the test material C 1s N 1s O 1s Zn 2p Cu 2p O / C CA 76.0 3.8 20.2 -- -- 0.27 Zn-MCA 64.8 14.2 17.3 3.7 -- 0.27 Zn-MCA-Cu 63.0 13.5 19.9 2.7 0.9 0.32 Zn-MCA-OTC 63.3 10.0 23.1 3.6 -- 0.36 Zn-MCA-Cu-OTC 61.2 13.2 20.3 2.5 2.8 0.33 O / C: The ratio of O 1s to C 1s content.

[0058] Example 5: Measurement using a Thermogravimetric Analyzer (TGA)

[0059] In Experiment 5, the materials prepared in Preparation Examples 1 to 3 were weighed using a five-position balance and placed in a crucible. Under a N2 environment, the initial temperature was set to 25 °C, and the temperature was increased to 700 °C at a rate of 10 °C per minute. The percentage of weight loss at different temperatures was analyzed to understand the thermal stability of the material. The thermogravimetric analyzer used in this experiment was purchased from Chi-Hau Electric Heating Co., Ltd., model TGA-9000.

[0060] To understand the thermal stability of the material, TGA was used in a N2 environment to heat it to 700 °C at a heating rate of 10 °C / min. The percentage of weight loss was calculated, and the causes of weight loss at each stage were analyzed. As shown in Figure 6, the weight loss of the material before and after modification can be divided into 2 to 3 stages. The first stage of CA was from 60 °C to 100 °C, with a loss of 6 wt%, mainly due to the loss of moisture. The second stage was from 210 °C to 350 °C, with a loss of 40 wt%, caused by the decomposition of chitosan and glutaraldehyde molecular chains. The third stage was from 360 °C to 700 °C, with a loss of 19 wt%, caused by the continued decomposition of chitosan at high temperatures after the material structure collapsed. The rate of loss and the specific gravity were slower than in the second stage. Finally, at 700 °C, CA had 35 wt% remaining. Zn-MOF exhibits only two weight loss stages. The first stage, from 400 °C to 490 °C, results in a 21 wt% loss, primarily due to the decomposition of organic functional groups within the structure. The second stage, from 610 °C to 700 °C, results in a 24 wt% loss, caused by the decomposition of the imidazole ring in the Zn-MOF structure. Ultimately, at 700 °C, Zn-MOF retains 55 wt%. Zn-MCA exhibits a first stage, from 400 °C to 480 °C, resulting in a 28 wt% loss due to the decomposition of organic molecular chains and functional groups. The second stage, from 480 °C to 580 °C, also results in a 28 wt% loss, caused by the decomposition of chitosan and the imidazole ring. The third stage, from 580 °C to 700 °C, results in a 4 wt% loss, caused by the decomposition of the remaining imidazole ring. Ultimately, at 700 °C, Zn-MCA retains 40 wt%. It was found that Zn-MOF-modified CA exhibits better thermal stability than CA. This is because Zn-MOF crystals cover the surface of CA, resulting in a higher decomposition temperature and a greater remaining weight compared to CA.

[0061] Table 3: TGA Analysis Results of CA, Zn-MOF, and Zn-MCA Test material Phase 1 Phase Two Phase Three Remaining amount @ 700 ℃ T1 (°C) △W1(wt %) T2 (°C) △W2(wt %) T3 (°C) △W3(wt %) (wt%) CA 60 ~ 100 6 210 ~ 350 40 360 ~ 700 19 35 Zn-MOF 490 ~ 610 twenty one 610 ~ 700 twenty four -- -- 55 Zn-MCA 400 ~ 480 28 480 ~ 580 28 580 ~ 700 4 40 T1, T2, and T3 represent the temperature ranges for the first, second, and third stages, respectively. △W1, △W2, and △W3 represent the weight losses for the first, second, and third stages, respectively.

[0062] Example 6: Determination using a nitrogen isotherm adsorption / desorption analyzer (BET)

[0063] In Experiment Six, the materials prepared in Examples One and Two were weighed using a five-position balance. The heating rate was set to 10 °C per minute, and the materials were degassed in a vacuum environment at 120 °C for 1440 minutes. The weight of the materials after degassed was recorded. N₂ adsorption / desorption experiments were conducted in a liquid nitrogen environment at -196 °C, with the pressure ratio controlled. Finally, the experimental results were substituted into the BET and BJH formulas to calculate the specific surface area, pore volume, and pore size distribution. The nitrogen isothermal adsorption / desorption analyzer used in this experiment was purchased from Micromeritics Inc., model ASAP 2020 N.

[0064] The specific surface area, pore size distribution, and total pore volume of Zn-MOF materials were analyzed using an N2 adsorption / desorption analyzer. Figure 7A shows that Zn-MOF exhibits Type IV adsorption / desorption curves, with significant N2 adsorption between P / P0 values ​​of 0.0 and 0.1 and 0.8 and 1.0, and a H3-type hysteresis loop. Figure 7B shows that the pore size is mainly distributed between 2 nm and 4 nm, indicating that Zn-MOF is a mesoporous material. t-Plot and BJH calculations revealed that the specific surface area of ​​Zn-MOF is 877.9 m² / g STP, the average pore size is 2.5 nm, and the total pore volume is 0.55 cm³ / g, as shown in Table 4. It is evident that Zn-MOF possesses a high specific surface area and small pore size. Loading it onto CA can increase the overall specific surface area and the number of small pores, thereby improving its adsorption performance for Cu(II) and OTC.

[0065] Table 4: Analysis results of N2 adsorption-desorption analysis of Zn-MOF Test material BET specific surface area (m²) 2 / g STP) Average pore size (nm) Total pore volume (cm³) 3 / g) Zn-MOF 877.94 2.5 0.55

[0066] Performance Analysis of Adsorption Materials

[0067] Experimental Example 7: Effect of Initial Concentration of Divalent Copper (Cu(II)) on Adsorption Performance

[0068] The adsorption reaction experiment used a test material with a dosage of 1 g / L, the temperature was fixed at 25 °C, the pH value was fixed at 5, and the adsorption time was 180 minutes. Under four different concentrations of Cu(II), the effect of aerogel material on the adsorption efficiency and adsorption capacity of Cu(II) was investigated. As shown in Figures 8A to 8D, the experimental results show that when the initial concentration of Cu(II) ions is 1 ppm, 2 ppm, 10 ppm, and 20 ppm (Figures 8A and 8C), the adsorption efficiencies of CA are 45.0%, 35.9%, 18.9%, and 13.1%, respectively, and the adsorption capacities are 0.45 mg / g, 0.74 mg / g, 2.09 mg / g, and 2.77 mg / g, respectively (Figure 8B); the adsorption efficiencies of Zn-MCA are 95.1%, 80.9%, 64.8%, and 55.1%, respectively, and the adsorption capacities are 0.97 mg / g, 1.69 mg / g, 6.48 mg / g, and 11.02 mg / g, respectively (Figure 8D).

[0069] The results above show that after modifying CA with Zn-MOF, the specific surface area of ​​the material is increased and more active sites are provided so that pollutants can be adsorbed on the surface of the material. The adsorption efficiency and adsorption capacity are greatly improved. Under different initial concentrations of Cu(II), the adsorption efficiency and adsorption capacity of Zn-MCA are 2-4 times higher than those of CA. It is known that MOF composite chitosan is of great help in the adsorption treatment of Cu(II).

[0070] As the initial concentration of Cu(II) increases, the adsorption efficiency of the aerogel material decreases. This is because the number of active sites on the material surface is limited; when the pollutant concentration increases, the material has insufficient capacity to process the remaining pollutants, leading to a decrease in adsorption efficiency. The relationship between adsorption capacity and initial concentration is the opposite of the relationship between adsorption efficiency and initial concentration. As the initial concentration of Cu(II) increases, the adsorption capacity of the aerogel material also increases. This is because the higher the pollutant concentration, the stronger the driving force from the solution to the material surface, resulting in a greater opportunity for the material to contact the pollutants, thus increasing the adsorption capacity.

[0071] Experimental Example 8: Effect of pH on Cu(II) Adsorption Efficiency

[0072] To investigate the effect of aerogel material on the adsorption efficiency of Cu(II) under different pH conditions, aerogel material with a dosage of 1 g / L was used, the temperature was fixed at 25 °C, the Cu(II) concentration was fixed at 2 and 10 ppm, and the adsorption time was 180 minutes. Since Cu(II) solution is more likely to form Cu(OH)2 precipitate when the pH value is greater than 6, the pH value of 2 to 5 was selected for the experiment. The pH value of Cu(II) solution was adjusted to 2, 3, 4 and 5 using 0.1M HCl or 0.1M NaOH. As shown in Figures 9A to 9D, the experimental results show that when the pH of the Cu(II) solution is 2, 3, 4, and 5, the adsorption efficiencies of CA are 14.5%, 32.5%, 33.3%, and 35.9%, with adsorption capacities of 0.37 mg / g, 0.65 mg / g, 0.73 mg / g, and 0.74 mg / g (Figure 9A); the adsorption efficiencies of Zn-MCA are 50.3%, 53.6%, 59.1%, and 64.8%, with adsorption capacities of 5.10 mg / g, 5.47 mg / g, 5.90 mg / g, and 6.48 mg / g (Figure 9C). Therefore, it can be seen that chitosan aerogel has the best adsorption efficiency at pH 5, both before and after modification.

[0073] The pH ZPC of the aerogel material was calculated using the initial pH value and the pH value after the adsorption experiment, as shown in Figure 9B. It can be seen that the CA material surface is uncharged at pH 3.9, positively charged when the pH value is less than 3.9, and negatively charged when the pH value is greater than 3.9. Therefore, the CA material has a better adsorption effect on Cu(II) when the pH value is greater than 3.9. That is, as the pH value increases, the adsorption efficiency and adsorption capacity of CA for Cu(II) increase. As shown in Figure 9D, the Zn-MCA surface is positively charged between pH 2 and 5. This may be because the modification process uses an in-situ growth immersion method, in which the chitosan aerogel is immersed in a methanol solution containing Zn-MOF, thus increasing the pH ZPC of Zn-MCA. However, as the pH value increases from 2 to 5, the positive charge on the material surface gradually decreases, the electrostatic repulsion between Zn-MCA and Cu(II) decreases, and the adsorption efficiency improves.

[0074] Experimental Example 9: Effect of Temperature on Cu(II) Adsorption Efficiency

[0075] The aerogel material adsorbent dosage was 1 g / L, the pH value was fixed at 5, the initial Cu(II) concentration was fixed at 2 and 10 ppm, the adsorption time was 180 minutes, and the temperatures were 15 ℃, 25 ℃, 35 ℃ and 45 ℃, respectively. The temperature effect was tested using a constant temperature shaker. When the temperature was 15 ℃, 25 ℃, 35 ℃ and 45 ℃, the adsorption efficiency of CA was 17.5%, 35.9%, 40.8% and 55.1%, and the adsorption capacity was 0.37 mg, 0.74 mg, 0.78 mg and 1.09 mg (Figure 10A); the adsorption efficiency of Zn-MCA was 55.5%, 64.8%, 72.9% and 85.0%, and the adsorption capacity was 5.55 mg / g, 6.48 mg / g, 6.63 mg / g and 6.75 mg / g (Figure 10B). It can be seen that the adsorption of Cu(II) by aerogel materials is an endothermic reaction. As the temperature rises, the collisions between molecules become more intense, which increases the chance of pollutants coming into contact with the adsorbent, and thus the adsorption efficiency also increases.

[0076] Experimental Example 10: Effect of Dosage on Cu(II) Adsorption Efficiency

[0077] To analyze the effect of different dosages on adsorption performance, the initial concentrations were fixed at 2 and 10 ppm, the adsorption time was 180 minutes, the pH was 5, the temperature was 25 ℃, and the dosages were 0.25 g / L, 0.5 g / L, 1 g / L, and 2 g / L, respectively. As shown in Figure 11A, the CA adsorption efficiencies were 12.3%, 22.6%, 35.9%, and 68.3%; the adsorption capacities were 0.99 mg / g, 0.90 mg / g, 0.74 mg / g, and 0.68 mg / g. As shown in Figure 11B, the Zn-MCA adsorption efficiencies were 25.4%, 48.5%, 64.8%, and 91.9%; the adsorption capacities were 10.8 mg / g, 9.7 mg / g, 6.48 mg / g, and 4.83 mg / g. As can be seen from the above, the adsorption capacity increases with increasing dosage because, at the same initial concentration, a larger dosage provides more active sites, thus enabling the adsorption of more Cu(II). Conversely, the adsorption capacity decreases with increasing dosage because the average Cu(II) content adsorbed per gram is lower, thus reducing the adsorption capacity. The crossover point between adsorption efficiency and adsorption capacity is approximately at dosages of 1.2 and 0.9 g / L. Therefore, the adjacent 1 g / L was selected as the dosage parameter for subsequent experiments.

[0078] Experimental Example 11: Dissociation of divalent zinc (Zn(II)) during the adsorption of Cu(II) by Zn-MCA

[0079] This experiment analyzed the changes in Zn(II) concentration in the waste liquid after the Zn-MCA adsorption of Cu(II) process to understand whether Zn(II) dissolution occurred in Zn-MCA (Zn content approximately 20 mg). As shown in Figure 12, when samples were taken at adsorption times of 0 minutes, 5 minutes, 10 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes, and 180 minutes, the Zn(II) concentration in the waste liquid after Cu(II) adsorption was 0.00 ppm, 0.70 ppm, 1.20 ppm, 1.58 ppm, 2.05 ppm, 2.41 ppm, 2.67 ppm, and 2.71 ppm, respectively. At an adsorption time of 180 minutes, the amount of Zn(II) dissolved from Zn-MCA in the waste liquid after Cu(II) adsorption was approximately 0.271 mg, or approximately 1.36%. The final cumulative concentration was 2.71 ppm, which is lower than the effluent standard of 3.5 mg / L and the drinking water standard of 5.0 mg / L.

[0080] Experimental Example Twelve: Recyclability of Cu(II) Adsorbed by Zn-MCA

[0081] To understand the reusability of Zn-MCA adsorbent for Cu(II), the Cu(II) concentration was fixed at 2 ppm, the Zn-MCA dosage was 1 g / L, the temperature was 25 ℃, the pH was 5, and the adsorption time was 180 minutes. Six reusability tests were conducted on Zn-MCA. After adsorption, the Zn-MCA was soaked in 0.1 M hydrochloric acid for 12 hours for desorption, and then washed with deionized water until neutral. Finally, it was placed in a 50°C oven to remove moisture, and its reusability was tested. As shown in Figure 13, after six reusability tests, the adsorption efficiency of Zn-MCA for Cu(II) decreased from 80.9% to 77.4%, a decrease of only 3.5%; the adsorption capacity decreased from 1.69 mg / g to 1.52 mg / g, a decrease of 0.17 mg / g, a decrease of only 10%. This indicates that Zn-MCA has good reusability. The main reason for the decrease in adsorption performance is that Cu(II) was not completely desorbed during regeneration, or that the ion exchange reaction was reduced due to the dissociation of Zn(II).

[0082] Experimental Example Thirteen: Effect of Initial OTC Concentration on Adsorption Performance

[0083] The aerogel dosage was fixed at 1 g / L, the temperature at 25 ℃, the pH value at 5, and the adsorption time at 120 minutes. The effect of concentration on the adsorption efficiency and adsorption capacity of the aerogel was analyzed under four different initial OTC concentrations. As shown in Figures 14A to 14D, when the initial OTC concentrations were 1 ppm, 2 ppm, 4 ppm, and 8 ppm, the CA adsorption efficiencies were 24.7%, 21.0%, 14.3%, and 10.0%, respectively, and the adsorption capacities were 0.27 mg / g, 0.47 mg / g, 0.63 mg / g, and 0.78 mg / g, respectively (Figure 14B); the Zn-MCA adsorption efficiencies were 91.8%, 88.9%, 68.3%, and 63.9%, respectively, and the adsorption capacities were 0.69 mg / g, 1.54 mg / g, 2.54 mg / g, and 4.27 mg / g, respectively (Figure 14D).

[0084] After modification of CA with Zn-MOF, the adsorption efficiency for OTC increased by 3 to 6 times, and the adsorption capacity increased by 2 to 5 times. This demonstrates that in-situ growth of Zn-MOF on CA not only increases the specific surface area of ​​the material but also provides a large number of active sites for OTC adsorption. Furthermore, as the initial concentration of OTC increases, the adsorption efficiency of Zn-MCA decreases. Since the number of active sites of the adsorbent is fixed, when all active sites are occupied by pollutants, the higher the initial concentration, the higher the remaining concentration, thus reducing the adsorption efficiency. However, as the initial concentration of OTC increases, the adsorption capacity of Zn-MCA increases because, under high concentration conditions, the driving force of pollutants towards the adsorbent surface increases, thereby increasing the adsorption capacity.

[0085] Experimental Example Fourteen: The Effect of pH Value on OTC Adsorption Efficiency

[0086] The adsorbent dosage was fixed at 1 g / L, the temperature at 25 ℃, the initial concentration at 2 ppm, and the adsorption time at 120 minutes. The effect of aerogel material on OTC adsorption efficiency at pH values ​​of 3, 5, 7, and 9 was investigated. As shown in Figures 15 and 16, OTC hydrolyzes at pH values ​​of 3.57, 7.49, and 9.44, resulting in different ionic charges of OTC in water at different pH values. As shown in Figures 17B and 17D, the pH ZPC of CA increases from 4.16 for CA to approximately 9 for Zn-MCA because CA is immersed in a methanol solution containing Zn-MOF, which increases the pH ZPC of the material. When the pH values ​​are 3, 5, 7, and 9, the adsorption efficiencies of CA are 13.6%, 21.0%, 16.5%, and 10.0%, respectively, and the adsorption capacities are 0.26 mg / g, 0.47 mg / g, 0.32 mg / g, and 0.21 mg / g (Figure 17A); the adsorption efficiencies of Zn-MCA are 79.5%, 88.9%, 71.7%, and 71.6%, respectively, and the adsorption capacities are 1.41 mg / g, 1.54 mg / g, 1.27 mg / g, and 1.25 mg / g (Figure 17C).

[0087] As can be seen from the above, both CA and Zn-MCA have the best adsorption efficiency at pH 5. At pH 3, because both the material surface and OTC are positively charged, they will electrostatically repel each other; at pH 5, OTC is uncharged, the CA surface is negatively charged, and the Zn-MCA surface is positively charged, so there will be electrostatic attraction; at pH 7 and 9, OTC is negatively charged, the CA surface is negatively charged, and the Zn-MCA surface is positively charged. CA and OTC electrostatically repel each other. Although the Zn-MCA surface is positively charged and there will be electrostatic attraction, the adsorption efficiency is lower than at pH 5 because the positive charge is weak.

[0088] Experimental Example 15: The Effect of Temperature on OTC Adsorption Efficiency

[0089] The concentrations were fixed at 2 ppm and 8 ppm, the pH value was 5, the aerogel dosage was 1 g / L, the adsorption time was 120 minutes, and the temperatures were 15 ℃, 25 ℃, 35 ℃, and 45 ℃. The effect of aerogel on OTC adsorption efficiency under different temperatures was analyzed. At 15 ℃, 25 ℃, 35 ℃, and 45 ℃, as shown in Figure 18A, the CA adsorption efficiency for OTC was 10.4%, 21.0%, 30.8%, and 45.6%, with adsorption capacities of 0.21 mg / g, 0.47 mg / g, 0.68 mg / g, and 0.90 mg / g, respectively. As shown in Figure 18B, the Zn-MCA adsorption efficiency for OTC was 50.9%, 63.9%, 72.2%, and 77.1%, with adsorption capacities of 4.07 mg / g, 4.27 mg / g, 5.70 mg / g, and 6.25 mg / g, respectively. It is known that the adsorption of OTC by aerogel is an endothermic process. When the temperature rises, the frequency of intermolecular collisions increases, giving OTC more opportunities to come into contact with the aerogel, thus increasing the adsorption efficiency.

[0090] Experimental Example Sixteen: Effect of Dosage on OTC Adsorption Performance

[0091] When the initial concentration of OTC was fixed at 2 and 8 ppm, the pH value was 5, the temperature was 25 ℃, and the adsorption time was 120 minutes, when the dosage was 0.25 g / L, 0.5 g / L, 1 g / L and 2 g / L, as shown in Figure 19A, the CA adsorption efficiency was 9.1%, 13.2%, 21.0% and 40.5%, and the adsorption capacity was 0.80 mg / g, 0.66 mg / g, 0.47 mg / g and 0.43 mg / g; as shown in Figure 19B, the Zn-MCA adsorption efficiency was 25.0%, 40.9%, 63.9% and 85.6%, and the adsorption capacity was 8.00 mg / g, 6.63 mg / g, 4.27 mg / g and 3.51 mg / g. The results showed that as the dosage increased, the adsorption efficiency also increased. Since the initial concentration was fixed, a higher dosage meant more active sites for pollutant adsorption. Conversely, the adsorption capacity decreased because although more adsorbent could provide a large number of active sites, the number of pollutants that could be adsorbed per gram decreased, thus reducing the adsorption capacity. The optimal aerogel dosages for CA and Zn-MCA were 1 and 0.8 g / L, respectively. 1 g / L was ultimately chosen as the aerogel dosage parameter for subsequent experiments.

[0092] Experimental Example 17: Zn(II) dissociation amount of OTC adsorbed by Zn-MCA

[0093] In this invention, after adsorbing OTC with Zn-MCA, the concentration of Zn(II) in the waste liquid was analyzed to understand the dissociation of Zn(II) after adsorbing OTC with Zn-MCA (Zn content approximately 20 mg), as shown in Figure 20. At adsorption times of 0 minutes, 5 minutes, 10 minutes, 30 minutes, 60 minutes, 90 minutes, and 120 minutes, the Zn(II) concentration in the solution was 0 ppm, 0.23 ppm, 0.56 ppm, 0.71 ppm, 0.81 ppm, 0.85 ppm, and 0.90 ppm, respectively. At an adsorption time of 120 minutes, the amount of Zn(II) dissolved from Zn-MCA in the waste liquid after OTC adsorption was approximately 0.09 mg, or approximately 0.45%. It was found that Zn(II) underwent some slight dissociation during the OTC adsorption process, but the concentration was still lower than the Zn(II) effluent standard of 3.5 mg / L and the drinking water standard of 5.0 mg / L. The proportion of Zn(II) leaching from Zn-MCA in the waste liquid after adsorbing pollutants was approximately three times higher than that of OTC (1.36%), with Cu(II) leaching being 1.36% higher. This difference is because the Zn(II) leaching during Cu(II) adsorption, besides the dissociation of Zn(II) within Zn-MCA itself (approximately 0.7 ppm; leaching amount approximately 0.07 mg), mainly originates from cation exchange between Zn(II) and Cu(II), resulting in a higher Zn(II) leaching amount. In other words, the Zn(II) leaching from OTC adsorption primarily stems from the dissociation of Zn(II) within the Zn-MCA material itself, with no cation exchange reaction participating in the adsorption process.

[0094] Experimental Example 18: Recyclability of Zn-MCA Adsorbed OTC

[0095] To test the reusability of Zn-MCA adsorbed OTC, the OTC concentration was fixed at 2 ppm, the temperature at 25 ℃, the pH at 5, the adsorbent dosage at 1 g / L, and the adsorption time at 120 minutes, for a total of 6 reusability tests. For the desorption experiment, the adsorbed Zn-MCA was immersed in 50% ethanol for 12 hours until the OTC dissolved from the material into the ethanol solution. The material was then removed, washed with deionized water until neutral, placed in a 50°C oven to remove moisture, and its reusability was tested. As shown in Figure 21, after 6 reusability tests, the adsorption efficiency of Zn-MCA for OTC decreased from 88.9% to 86.4%, a decrease of only 2.5%; the adsorption capacity decreased from 1.54 mg / g to 1.45 mg / g, a decrease of only 0.09 mg / g (approximately 5.8%), indicating that Zn-MCA has good reusability. After six reuse tests, the adsorption performance for OTC only decreased slightly. The main reason for the decrease was that OTC was not completely desorbed during regeneration.

[0096] Experimental Example 19: Effect of simultaneous adsorption of Cu(II) and OTC by Zn-MCA on adsorption capacity

[0097] The Zn-MCA dosage was 1 g / L, the temperature was fixed at 25 ℃, the pH value was 5, and the Cu(II) concentrations were 0 ppm, 1 ppm, 2 ppm, 10 ppm and 20 ppm, and the OTC concentrations were 0 ppm, 1 ppm, 2 ppm, 4 ppm and 8 ppm, respectively. After fixing the Cu(II) and OTC concentrations at 2 ppm, the concentration of another pollutant was changed. As shown in Figure 22A, when the OTC concentration was fixed (2 ppm), the adsorption efficiency of Zn-MCA for OTC was 88.9%, 53.7%, 51.5%, 50.0% and 29.4% with Cu(II) concentrations of 0 ppm, 1 ppm, 2 ppm, 10 ppm and 20 ppm, respectively; the adsorption capacity was 1.54 mg / g, 1.07 mg / g, 1.03 mg / g, 1.00 mg / g and 0.62 mg / g. Compared to independent adsorption, the ratio of adsorption efficiency to adsorption capacity for simultaneous adsorption was 0.33 times and 0.40 times, respectively. As shown in Figure 22B, with a fixed Cu(II) concentration (2 ppm), the adsorption efficiencies of Zn-MCA for Cu(II) were 80.9%, 80.0%, 79.4%, 75.4%, and 72.4% for OTC concentrations of 0 ppm, 1 ppm, 2 ppm, 4 ppm, and 8 ppm, respectively; the adsorption capacities were 1.69 mg / g, 1.66 mg / g, 1.60 mg / g, 1.53 mg / g, and 1.23 mg / g, respectively. Compared to independent adsorption, the ratio of adsorption efficiency to adsorption capacity for simultaneous adsorption was 0.90 times and 0.73 times, respectively. It is known that when Cu(II) and OTC are simultaneously adsorbed, they compete for adsorption due to their similar electrical properties. However, the effect on the adsorption performance of Cu(II) is relatively minor. Therefore, when both pollutants are present in wastewater, Zn-MCA will preferentially adsorb Cu(II). [Simplified Explanation of the Diagram]

[0098] Figures 1A and 1B are SEM images of the chitosan aerogel (CA) of the present invention at 50x and 100x magnification, respectively; Figures 1C and 1D are SEM images of the zinc-modified chitosan aerogel (Zn-MCA) of the present invention at 50x and 100x magnification, respectively; Figures 2A and 2B are SEM images of the adsorption of divalent copper (Cu(II)) by Zn-MCA of the present invention at 50x and 100x magnification, respectively; Figures 2C and 2D are SEM images of the adsorption of oxytetracycline (OTC) by Zn-MCA of the present invention at 50x and 100x magnification, respectively; Figures 2E and 2F are SEM images of the adsorption of Cu(II) and OTC by Zn-MCA of the present invention at 50x and 100x magnification, respectively; Figure 3A is an FTIR image of CA, Zn-MOF, and Zn-MCA of the present invention; Figure 3B shows the FTIR spectra of OTC, Zn-MCA, Zn-MCA adsorbing Cu (Zn-MCA-Cu), Zn-MCA adsorbing OTC (Zn-MCA-OTC), and Zn-MCA simultaneously adsorbing Cu and OTC (Zn-MCA-Cu-OTC) of the present invention; Figure 4A shows the XRD patterns of Zn-MOF and JCPDS: 00-062-1030 ZIF-8 of the present invention; Figure 4B shows the XRD patterns of CA, Zn-MCA, Zn-MOF, and chitosan of the present invention; Figure 5 shows the total energy spectrum of CA, Zn-MCA, Zn-MCA adsorbing Cu (Zn-MCA-Cu), Zn-MCA adsorbing OTC (Zn-MCA-OTC), and Zn-MCA simultaneously adsorbing Cu and OTC (Zn-MCA-Cu-OTC) of the present invention; Figure 6 shows the TGA analysis results of CA, Zn-MOF, and Zn-MCA of the present invention. Figures 7A and 7B, in sequence, show the N₂ adsorption-desorption curves and pore size distribution of the Zn-MOF of the present invention; Figures 8A and 8B, in sequence, show the hourly relative concentration changes of Cu(II) adsorbed by CA of the present invention and the relationship between initial concentration and adsorption performance; Figures 8C and 8D, in sequence, show the hourly relative concentration changes of Cu(II) adsorbed by Zn-MCA of the present invention and the relationship between initial concentration and adsorption performance; Figures 9A and 9B, in sequence, show the adsorption efficiency and adsorption capacity changes of CA for Cu(II) of the present invention and the zero-point charge plot; Figures 9C and 9D, in sequence, show the adsorption efficiency and adsorption capacity changes of Zn-MCA for Cu(II) of the present invention and the zero-point charge plot; Figures 10A and 10B, in sequence, show the temperature effect on the adsorption efficiency of CA and Zn-MCA for Cu(II) of the present invention; Figures 11A and 11B, in sequence, show the dosage effect on the adsorption efficiency of CA and Zn-MCA for Cu(II) of the present invention. Figure 12 is a curve of Zn(II) dissolution concentration during the Zn-MCA adsorption of Cu(II) process of the present invention; Figure 13 is a graph showing the relationship between the number of reuses and the adsorption efficiency of Zn-MCA adsorbing Cu(II) in the present invention.Figures 14A and 14B, in sequence, show the hourly relative concentration changes of oxytetracycline (OTC) adsorbed by CA according to the present invention, and the relationship between initial concentration and adsorption performance; Figures 14C and 14D, in sequence, show the hourly relative concentration changes of OTC adsorbed by Zn-MCA according to the present invention, and the relationship between initial concentration and adsorption performance; Figure 15 is an ionic strength curve of OTC at different pH values ​​(Punamiya et al., 2013); Figure 16 shows the hydrolysis reaction of OTC at different pH values ​​(Liu et al., 2015); Figures 17A and 17B, in sequence, show the adsorption efficiency and adsorption capacity changes of CA for OTC according to the present invention, and the zero-point charge plot; Figures 17C and 17D, in sequence, show the adsorption efficiency and adsorption capacity changes of Zn-MCA for OTC according to the present invention, and the zero-point charge plot; Figures 18A and 18B, in sequence, show the temperature effect on the adsorption efficiency of CA and Zn-MCA for OTC according to the present invention. Figures 19A and 19B, respectively, show the effect of dosage of CA and Zn-MCA on the adsorption efficiency of OTC in this invention; Figure 20 is a Zn(II) dissolution concentration curve during the adsorption of OTC by Zn-MCA in this invention; Figure 21 shows the relationship between the number of reuses and the adsorption efficiency of OTC adsorbed by Zn-MCA in this invention; Figures 22A and 22B, respectively, show the effect of Cu(II) on the adsorption efficiency of OTC and the effect of OTC on the adsorption efficiency of Cu(II) when Zn-MCA simultaneously adsorbs Cu(II) and OTC in this invention.

Claims

1. A modified chitosan aerogel, comprising: Zinc-based modified chitosan aerogel (Zn-MCA) modified with zinc-based metal-organic framework (Zn-MOF) exhibits absorption peaks in the following wavenumber regions when measured by Fourier transform infrared spectroscopy (FTIR): 3100 to 3400 cm⁻¹, 2950 cm⁻¹ ± 4 cm⁻¹, 1658 cm⁻¹ ± 4 cm⁻¹, 1592 cm⁻¹ ± 4 cm⁻¹, 1383 cm⁻¹ ± 4 cm⁻¹, 1020 cm⁻¹ ± 4 cm⁻¹, 997 cm⁻¹ ± 4 cm⁻¹, 757 cm⁻¹ ± 4 cm⁻¹, and 691 cm⁻¹ ± 4 cm⁻¹.

2. The modified chitosan aerogel as described in claim 1, wherein, When analyzed by X-ray diffraction (XRD), the zinc-modified chitosan aerogel (Zn-MCA) showed characteristic peaks at the following 2θ positions: 21.0°±0.5°, 7.3°±0.5°, 10.7°±0.5°, 12.9°±0.5°, 13.8°±0.5°, 15.3°±0.5°, 17.8°±0.5°, 26.0°±0.5°, and 29.2°±0.5°.

3. The modified chitosan aerogel as described in claim 1, wherein, When the surface elements of the zinc-based modified chitosan aerogel (Zn-MCA) were measured by X-ray photoelectron spectrometry (XPS), the atomic percentages were found to be 64.8±5% C 1s, 14.2±5% N 1s, 17.3±5% O 1s, and 3.7±5% Zn 2p.

4. A method for preparing a modified chitosan aerogel, comprising the following steps: Dissolution and cross-linking steps: Chitosan powder is added to an aqueous solution of organic acid to completely dissolve the chitosan and form a chitosan solution; A crosslinking agent is added to the chitosan solution to initiate a crosslinking reaction. After stirring until homogeneous, the solution is subjected to ultrasonic vibration to remove air bubbles and allowed to stand until a solid hydrogel is formed. The hydrogel is then cured and dried by immersing it in an alkaline solution to solidify it, followed by washing with deionized water until neutral. The cured material is then freeze-dried to obtain a chitosan aerogel. A metal precursor treatment step involves dissolving a zinc salt compound in an organic solvent to form a zinc precursor solution. The chitosan aerogel is then contacted with this zinc precursor solution for sufficient adsorption, forming a zinc-ion-containing chitosan aerogel. Finally, a metal-organic framework (MOF) growth step involves dissolving an imidazole compound in an organic solvent to form a MOF ligand solution, which is then added to the zinc-ion-containing chitosan aerogel to allow MOF crystals to grow on the surface of the aerogel, resulting in a preliminary material. Cleaning and drying steps: The initial material is washed with deionized water to remove unreacted MOF precursors, and then freeze-dried to obtain zinc-modified chitosan aerogel (Zn-MCA), one of the chitosan aerogels composed of zinc-based metal-organic framework (Zn-MOF) composites; wherein the content of Zn-MOF in the chitosan aerogel is saturated, and based on the total weight of the zinc-modified chitosan aerogel (Zn-MCA) being 100wt%, the loading of Zn-MOF in the chitosan aerogel ranges from 20 wt% to 50 wt%.

5. The method for preparing the modified chitosan aerogel as described in claim 4, wherein, In the dissolution and crosslinking steps, the organic acid aqueous solution is acetic acid (CH3COOH) with a concentration of 0.2M; the crosslinking agent is glutaraldehyde (C5H8O2); in the hydrogel curing and drying steps, the alkaline solution is sodium hydroxide (NaOH) with a concentration of 0.1M; in the metal precursor treatment step, the zinc salt compound is zinc nitrate hexahydrate (Zn(NO3)2·6H2O); the organic solvent is methanol (CH3OH) solution; in the metal-organic framework (MOF) growth step, the imidazole compound is 2-methylimidazole (C4H6N2); the organic solvent is methanol (CH3OH) solution.

6. The method for preparing the modified chitosan aerogel as described in claim 4, wherein, Based on a total weight of 100 wt% for the zinc-modified chitosan aerogel (Zn-MCA), the loading of Zn-MOF in the chitosan aerogel ranges from 35 wt%.

7. Use of a modified chitosan aerogel as described in any one of claims 1 to 3 for adsorbing divalent copper (Cu(II)) ions in waste liquid; wherein, When the initial concentration of the divalent copper ion is 1 ppm to 20 ppm, the pH of the waste liquid is 2 to 5, the dosage of the zinc-based modified chitosan aerogel in each liter of waste liquid is 0.25 g to 2.0 g, the adsorption temperature is 15 °C to 45 °C, and the adsorption time is 180 minutes, the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for the Cu(II) ion reaches 95.1%.

8. Use of a modified chitosan aerogel prepared by any one of claims 4 to 6 for adsorbing divalent copper (Cu(II)) ions in waste liquid; wherein, When the initial concentration of the divalent copper ion is 1 ppm to 20 ppm, the pH of the waste liquid is 2 to 5, the dosage of the zinc-based modified chitosan aerogel in each liter of waste liquid is 0.25 g to 2.0 g, the adsorption temperature is 15 °C to 45 °C, and the adsorption time is 180 minutes, the adsorption efficiency of the zinc-based modified chitosan aerogel (Zn-MCA) for the Cu(II) ion reaches 95.1%.

9. Use of a modified chitosan aerogel as described in any one of claims 1 to 3 for adsorbing oxytetracycline (OTC) from waste liquid; wherein, When the initial concentration of oxytetracycline is 1 ppm to 8 ppm, the pH of the waste liquid is 3 to 9, the dosage of zinc-modified chitosan aerogel in each liter of waste liquid is 0.25 g to 2.0 g, the adsorption temperature is 15 °C to 45 °C, and the adsorption time is 120 minutes, the adsorption efficiency of zinc-modified chitosan aerogel (Zn-MCA) for oxytetracycline reaches 91.8%.

10. Use of a modified chitosan aerogel prepared by any one of claims 4 to 6 for adsorbing oxytetracycline (OTC) in waste liquid; wherein, When the initial concentration of oxytetracycline is 1 ppm to 8 ppm, the pH of the waste liquid is 3 to 9, the dosage of zinc-modified chitosan aerogel in each liter of waste liquid is 0.25 g to 2.0 g, the adsorption temperature is 15 °C to 45 °C, and the adsorption time is 120 minutes, the adsorption efficiency of zinc-modified chitosan aerogel (Zn-MCA) for oxytetracycline reaches 91.8%.